2008
DOI: 10.1177/0044118x08318117
|View full text |Cite
|
Sign up to set email alerts
|

The Protective and Risk Effects of Parents and Peers on Substance Use, Attitudes, and Behaviors of Mexican and Mexican American Female and Male Adolescents

Abstract: This study explores the extent to which parental and peer behaviors and norms may affect substance use, personal anti-drug norms and intentions to use drugs in a group of Mexican heritage preadolescents in the Southwest, and whether these parental and peer influences differ according to gender. Secondary data from a randomized trial of a drug prevention program was used. The sample consisted of 2,733 adolescents. The outcomes were recent alcohol, cigarette, and marijuana use, personal anti-drug norms and inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
3
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 69 publications
4
84
3
4
Order By: Relevance
“…The few studies that investigated cannabis-specific parenting found that parental unfavorable attitudes toward cannabis use (Bahr et al, 2005;Oesterle et al, 2012;Olsson et al, 2003) and parents' anger in response to drug use (Parsai et al, 2009) were negatively associated with adolescent cannabis use. Moreover, Miller-Day (2008) found that, after identifying seven parental strategies to deal with substance use, setting a "no tolerance rule" was the only effective strategy associated with less cannabis use among university students.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that investigated cannabis-specific parenting found that parental unfavorable attitudes toward cannabis use (Bahr et al, 2005;Oesterle et al, 2012;Olsson et al, 2003) and parents' anger in response to drug use (Parsai et al, 2009) were negatively associated with adolescent cannabis use. Moreover, Miller-Day (2008) found that, after identifying seven parental strategies to deal with substance use, setting a "no tolerance rule" was the only effective strategy associated with less cannabis use among university students.…”
Section: Introductionmentioning
confidence: 99%
“…Although substance use rates among Latinos=as tend to decrease by the time they reach 12th grade, Johnston and colleagues (2012) suggested that this perceived decrease might be artificially driven by the fact that many of these surveys do not include high school dropouts, of which Latinos=as comprise a sizable percentage. Alternatively, Prado, Szapocznik, Maldonado-Molina, Schwartz, and Pantin (2008) suggested that Latino=a students may engage in substance use earlier in their developmental process, which in turn magnifies detrimental effects and problematic outcomes, which manifests in their late-adolescent years (Gale, Lenardson, Lambert, & Hartley, 2012;Parsai, Voisine, Marsiglia, Kulis, & Nieri, 2009). …”
mentioning
confidence: 99%
“…Authors of several studies have also identified alcohol drinking among peers or friends as another very important factor in the context of alcohol drinking among children (26,27). The results of another study point to the fact that if siblings drank alcohol, there was a significantly increased chance of respondent's alcohol abuse (24).…”
Section: Discussionmentioning
confidence: 99%